KARAKTERISTIK MORFOLOGI ULAR FAMILIA ELAPIDAE DI KAMPUS UNIVERSITAS ANDALAS LIMAU MANIH PADANG - Reza, Fachrul; Tjong, Djong Hon; Novarino, Wilson (Sainstek : Jurnal Sains dan Teknologi, 2016)
Research on the Snakes Morphological Characteristics on Campus of Andalas University Limau Manih had been done. The research was conducted using survey method and Dissemination of Information to Public accompanied by morphometric measurements and descriptions. The results of the research that had been done caught 2 species that consist of one family namely Elapidae. This family is refer to snakes which has neurotoxin venom glands, no loreal scalation, and mostly teresterial. Maticora bivirgata flaviceps (Cantor, 1839) which has no loreal scale, red coloration on tail, and head; Naja sumatrana M?ller, 1887 which has no loreal scale, black coloration with yellow coloration on it?s hood, and yelowish head.